Stat3 activation is critical for pluripotency maintenance. Issue 2 (7th September 2018) - Zhang, Yan; Wang, Dan; Xu, Jia; Wang, Yuebing; Ma, Fengxia; Li, Zongjin; Liu, Na
Abstract: Signal transducer and activator of transcription 3 (Stat3) is a cytoplasmic transcription with many important functions, including regulation of cell proliferation, differentiation, survival, angiogenesis, and immune response. Besides, it plays critical roles in regulating the pluripotency. With the ability of self‐renewal and differentiation, embryonic stem (ES) cells provide an unlimited source for cell transplantation. ES cells can maintain its undifferentiated state with leukemia inhibitory factor, the role which is achieved by the activation of the Stat3 pathway. Moreover, Stat3 activation is necessary for the naïve state maintenance of the ES cells and somatic stem cells reprogramming. This study presents an overview of the critical roles of Stat3 activation in the pluripotency maintenance of ES cells, somatic cell reprogramming, and naïve‐primed pluripotent states conversion of ES cells. Abstract : This study presents an overview of the critical roles of signal transducer and activator of transcription 3 (Stat3) activation in the pluripotency maintenance of embryonic stem (ES) cells, somatic cell reprogramming, and naïve‐primed pluripotent states conversion of ES cells.